PEMBERDAYAAN EKONOMI MASYARAKAT DESA TANJUNG PAKIS AJI MELALUI KEGIATAN SOSIALISASI PENGEMASAN DAN PEMASASRAN GULA AREN - Ratih, Ratih Ratih; Yasmiatun, Yasmiatun; Sari, Zuliana Dwi Ratna; Afrianingsih, Anita; Farida, Yushinta Eka (Journal of Dedicators Community, 2022)
The Community Service Program was carried out in Tanjung Pakis Aji Jepara Village by selecting palm sugar partners. Based on the observations that we have done, there are several priority problems to be resolved in this KKN program, namely the limitations of palm sugar, palm sugar printing and packaging that is too simple, marketing that is only done traditionally, and there is no product identity. In this activity we provide several solutions to problems that exist in partners, including 1) innovating palm sugar molds which were originally round into a more economical shape for easy packaging. 2) in terms of packaging, it is packed using plastic with a weight of 250 grams and 500 grams. 3) put a label on the package. 4) marketing palm sugar through social media so that palm sugar can be known to the wider community. The purpose of service in palm sugar partners is to help find solutions to problems that exist in partners. In addition, to improve student skills in solving problems in society.